2005
DOI: 10.1080/13549839.2005.9684248
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Monitoring in Support of Local Sustainability

Abstract: Community-based monitoring (CBM) activities in Canada are increasing. A conceptual framework developed for and used to guide a pilot CBM project in 31 Canadian communities is evaluated. The framework provided the strategic direction necessary for successful implementation of the pilot and proved useful in the training of community coordinators hired for the project. Limitations of the framework include its inadequate attention to community diversity, its linearity, and insufficient expression of the adaptive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…First, the results of community-based efforts are not always shared widely beyond the community level (Sharpe and Conrad, 2006). Moreover, since national funding networks were originally designed to support the efforts of government and research institutions, community-led CBM initiatives that lack direct connections to these institutions face a relative disadvantage (Pollock and Whitelaw, 2005;Berkes et al, 2007). Third, in our experience, a bias remains in the scientific community against monitoring done by community residents who lack formal training in data collection and analysis.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…First, the results of community-based efforts are not always shared widely beyond the community level (Sharpe and Conrad, 2006). Moreover, since national funding networks were originally designed to support the efforts of government and research institutions, community-led CBM initiatives that lack direct connections to these institutions face a relative disadvantage (Pollock and Whitelaw, 2005;Berkes et al, 2007). Third, in our experience, a bias remains in the scientific community against monitoring done by community residents who lack formal training in data collection and analysis.…”
Section: Introductionmentioning
confidence: 90%
“…Robust community engagement is a key factor in the long-term viability of CBM initiatives (Pollock and Whitelaw, 2005;Danielsen et al, 2014b). Researchers seeking to partner or establish monitoring programs with communities are most successful when they have a strong understanding of community needs and expectations (Gearheard and Shirley, 2007), take an open and engaged approach to communication with community members (Pearce et al, 2009), and are flexible and adaptive (Pollock and Whitelaw, 2005).…”
Section: Community Engagement and The Utilization Of Community-based mentioning
confidence: 99%
See 1 more Smart Citation
“…Still others secured funds to build a cabin for use by tourists and developed jewelry to sell to visitors. Other researchers reported increased social capital outcomes related to aspects of social capital such as increased size of personal networks (Overdevest et al 2004, Gooch 2005, Pollock and Whitelaw 2005, Jones et al 2006, Measham and Barnett 2008, Koss and Kingsley 2010, development of partnerships (Sharpe et al 2000, Savan et al 2003, and community influence (Pollock andWhitelaw 2005, Jones et al 2006).…”
Section: Increase In Social Capitalmentioning
confidence: 99%
“…Most have concluded that, with appropriate resourcing and robust protocols, volunteer data agree closely enough with professional data for use in government http://www.ecologyandsociety.org/vol21/iss4/art32/ Involving community members in monitoring increases not only their ability to contribute data, but also their ability to discuss their knowledge with experts (described as "interactional expertise" by Carolan 2006). Community members participating in environmental monitoring also commonly show increased scientific literacy, greater awareness of local ecosystems and wider environmental issues, stronger social networks including relationships with local government, and greater interest in freshwater planning (Bliss et al 2001, Savan et al 2003, Overdevest et al 2004, Pollock and Whitelaw 2005, Stepenuck and Green 2015, Peters et al 2015b. All of these benefits may lead to more effective community engagement with government in freshwater decision making.…”
Section: Introductionmentioning
confidence: 99%